PENGELOLAAN SAMPAH SECARA BERSAMA: PERAN PEMERINTAH DAN KESADARAN MASYARAKAT - . Hamdan; Denny Nazaria Rifani; Andi Muhammad Jalaluddin; . Rudiansyah (Jurnal Paradigma (JP), 2019)
In the construction of urban settlement coaching, efforts must be made to improve public service, including environmental management. Waste problems are closely related to environmental cleanliness. This study examines the need for joint waste management, between government and the community to achieve success. The city of Samarinda and its residents who undergo daily activities that produce waste, need better waste management efforts to achieve the fulfillment of the need for a clean and healthy urban environment. Especially when the awareness of the community is known to be still low in terms of concern for the government’s efforts in waste management which includes waste reduction and handling activities. Keywords: waste management, public attitude.